Association between humidifier disinfectant exposure during infancy and subsequent neuropsychiatric outcomes during childhood: a nation-wide cross-sectional study - Ju Hee Kim; Sihyeong Park; Eun Kyo Ha; Dong Keon Yon; Seung Won Lee; Hyun Yong Koh; Man Yong Han (BMC, 2021)
Abstract Background The purpose was to determine the association between infant exposure to humidifier disinfectant (HD) with neuropsychiatric problems in pre-school children. Methods A total of 2,150 children (age 4-11 months) were enrolled in the Panel Study of Korean Children (PSKC) study. The Korean version of the Child Behavior Checklist (CBCL) was used for assessments of neuropsychiatric problems. 1,113 children who participated in all the first to third PSKC studies and answered a question about HD exposure were finally enrolled. Results There were 717 (64.5%) children in non-HD group who were not exposed to HD and 396 (35.5%) in HD group with former exposure to HD. Exposure to HD was associated with total neuropsychiatric problems (adjusted odds ratio, aOR = 1.54, 95% CI = 1.15-2.06), being emotionally reactive (aOR = 1.55, 95% CI = 1.00-2.39), having attention problems (aOR = 1.96, 95% CI = 1.10-3.47), having oppositional defiant problems (aOR = 1.70, 95% CI = 1.07-2.71), and having attention deficit/hyperactivity problems (aOR = 11.57, 95% CI = 1.03-2.38). The risks for neuropsychiatric problems were clearly increased in boy, firstborn, and secondary smoker. Conclusions Exposure to HD during early childhood had a potential association with subsequent behavioral abnormalities.